Pakistan’s Strategic Calculus: Navigating the Iran-Saudi Rivalry - Dr. Muhammad Naveed Ul Hasan Shah; Mohsin Niaz; Ataka Zahra (Journal of Religion and Society, 2025)
This research article investigates Pakistan's intricate foreign policy calculus in balancing its relations with Iran and Saudi Arabia amidst their protracted rivalry. The study employs a qualitative approach, drawing upon an extensive review of scholarly literature and policy analyses to understand the historical evolution of the Iran-Saudi conflict, the multifaceted dimensions of Pakistan's bilateral ties with each nation, and the resultant domestic and regional implications. The findings reveal that Pakistan's foreign policy is characterized by a pragmatic "neutrality-cum-balancing" strategy, a strategic imperative driven by geopolitical compulsions, economic dependencies, and internal sectarian vulnerabilities. While this adaptive approach has enabled Pakistan to maintain crucial bilateral ties and contribute to regional de-escalation efforts, it faces escalating challenges from external ideological influences and the complexities of global power dynamics. The article concludes that sustaining this delicate equilibrium necessitates a continuous recalibration of Pakistan's diplomatic and economic strategies to safeguard its national interests and foster regional stability. Keywords: Pakistan Foreign Policy, Iran-Saudi Rivalry, Regional Stability, Sectarian Dynamics, Strategic Balancing Middle East Geopolitics